TRPC4- and TRPC4-containing channels - Freichel, Marc; Tsvilovskyy, Volodymyr; Camacho Londoño, Juan Eduardo (Handbook of experimental pharmacology, 2014)
TRPC4 proteins comprise six transmembrane domains, a putative pore-forming region, and an intracellularly located amino- and carboxy-terminus. Among eleven splice variants identified so far, TRPC4α and TRPC4β are the most abundantly expressed and functionally characterized. TRPC4 is expressed in various organs and cell types including the soma and dendrites of numerous types of neurons; the cardiovascular system including endothelial, smooth muscle, and cardiac cells; myometrial and skeletal muscle cells; kidney; and immune cells such as mast cells. Both recombinant and native TRPC4-containing channels differ tremendously in their permeability and other biophysical properties, pharmacological modulation, and mode of activation depending on the cellular environment. They vary from inwardly rectifying store-operated channels with a high Ca(2+) selectivity to non-store-operated channels predominantly carrying Na(+) and activated by Gαq- and/or Gαi-coupled receptors with a complex U-shaped current-voltage relationship. Thus, individual TRPC4-containing channels contribute to agonist-induced Ca(2+) entry directly or indirectly via depolarization and activation of voltage-gated Ca(2+) channels. The differences in channel properties may arise from variations in the composition of the channel complexes, in the specific regulatory pathways in the corresponding cell system, and/or in the expression pattern of interaction partners which comprise other TRPC proteins to form heteromultimeric channels. Additional interaction partners of TRPC4 that can mediate the activity of TRPC4-containing channels include (1) scaffolding proteins (e.g., NHERF) that may mediate interactions with signaling molecules in or in close vicinity to the plasma membrane such as Gα proteins or phospholipase C and with the cytoskeleton, (2) proteins in specific membrane microdomains (e.g., caveolin-1), or (3) proteins on cellular organelles (e.g., Stim1). The diversity of TRPC4-containing channels hampers the development of specific agonists or antagonists, but recently, ML204 was identified as a blocker of both recombinant and endogenous TRPC4-containing channels with an IC50 in the lower micromolar range that lacks activity on most voltage-gated channels and other TRPs except TRPC5 and TRPC3. Lanthanides are specific activators of heterologously expressed TRPC4- and TRPC5-containing channels but can block individual native TRPC4-containing channels. The biological relevance of TRPC4-containing channels was demonstrated by knockdown of TRPC4 expression in numerous native systems including gene expression, cell differentiation and proliferation, formation of myotubes, and axonal regeneration. Studies of TRPC4 single and TRPC compound knockout mice uncovered their role for the regulation of vascular tone, endothelial permeability, gastrointestinal contractility and motility, neurotransmitter release, and social exploratory behavior as well as for excitotoxicity and epileptogenesis. Recently, a single-nucleotide polymorphism (SNP) in the Trpc4 gene was associated with a reduced risk for experience of myocardial infarction.